A novel DNA damage repair-related gene signature predicting survival, immune infiltration and drug sensitivity in cervical cancer based on single cell sequencing - Xiang, Xiaoqing; Kang, Jiawen; Jiang, Jingwen; Zhang, Yaning; Zhang, Yong; Li, Lesai; Peng, Xiaoning (Frontiers in Immunology, 2023)
Background Aberrant DNA damage repair (DDR) is one of the hallmarks of tumors, and therapeutic approaches targeting this feature are gaining increasing attention. This study aims to develop a signature of DDR-related genes to evaluate the prognosis of cervical cancer (CC). Methods Differentially expressed genes were identified between high and low DDR groups of cells from the single-cell RNA sequencing dataset GSE168652 based on DDR scores. Using the ssGSEA and WGCNA methods, DDR-related differentially expressed genes were identified from different patients within the TCGA-CESC cohort. Using Cox analysis and LASSO regression analysis, a DDR-related gene signature was constructed based on the intersection of two groups of differentially expressed genes and DDR-related genes from WGCNA, and validated in GSE52903. Immune cell infiltration analysis, mutation analysis, survival analysis, drug sensitivity analysis, etc., were performed in different groups which were established based on the DDR gene signature scoring. A key gene affecting prognosis was selected and validated through biological experiments such as wound healing, migration, invasion, and comet assays. Results A novel DDR-related signature was constructed and the nomogram results showed this signature performed better in predicting prognosis than other clinical features for CC. The high DDR group exhibited poorer prognosis, weaker immune cell infiltration in the immune microenvironment, lower expression of immune checkpoint-related genes, lower gene mutation frequencies and more sensitivity to drugs such as BI.2536, Bleomycin and etc. ITGB1, ZC3H13, and TOMM20 were expressed at higher levels in CaSki and HeLa cells compared to ECT1 cells. Compared with the native CaSki and HeLa cells, the proliferation, migration, invasion and DDR capabilities of CaSki and HeLa cell lines with ITGB1 suppressed expression were significantly decreased. Conclusion The 7 DDR-related gene signature was an independent and powerful prognostic biomarker that might effectively evaluate the prognosis of CC and provide supplementary information for a more personalized evaluation and precision therapy. ITGB1 was a potential candidate gene that may affect the DDR capacity of CC cells, and its mechanism of action was worth further in-depth study.